Effect of Financial Literacy, Financial Management Application, and Savings Behavior on Retirement Readiness Moderated by Financial Knowledge and Financial Attitude (Study on Female Civil Servant in Waropen Regency) - Renta Uli Nababan; Said Kelana Asnawi; Agus Susanto (Budapest International Research and Critics University, 2022)
Female civil servants tend to have lower levels of retirement readiness than men. This study examines the factors influencing retirement readiness: financial literacy, financial management application, and saving behavior. Moreover, this study also examines financial knowledge and attitudes as moderating variables. The research design uses quantitative research with a causal approach. The sample of this study was 286 female civil servants in the Waropen Regency. Data analysis uses the SEM-PLS method with the help of SmartPLS3 software. The analysis results show that financial literacy, financial management application, and saving behavior positively and significantly affect retirement readiness. Financial knowledge can moderate the financial management application to retirement readiness, but financial attitudes cannot moderate saving behavior towards retirement readiness. The study results provide significant implications for the government and management of the public sector, especially in Waropen Regency, to improve the retirement readiness of female civil servants.